Behavior of Trichogramma atopovirilia Oatman & Platner and T. pretiosum Riley (Hymenoptera: Trichogrammatidae) on Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) egg masses - E. B Beserra; C. T. Dias; J. R. P. Parra (Brazilian Journal of Biology)
In this study we analyzed the impact of physical barriers of Spodoptera frugiperda (J. E. Smith) egg-masses on the behavior of Trichogramma atopovirilia Oatman & Platner and Trichogramma pretiosum Riley. The duration of drumming, drilling, oviposition, period spent over the egg-mass, and interval between parasitized eggs were timed, and the number of parasitized eggs were recorded. The presence of scales on the egg-masses caused a significant increase in the time spent by both parasitoids on each process and a decrease in the residence time over the egg-mass and in the number of parasitized eggs, with an increase in the number of egg layers. There was a significant decrease in the number of parasitized eggs in relation to egg-masses with one layer and no scales. We observed that the physical barriers in fall armyworm egg-masses changed the behavior of T. atopovirilia and T. pretiosum, affecting their parasitization capacity.